2018
DOI: 10.1021/acs.joc.8b00625
|View full text |Cite
|
Sign up to set email alerts
|

Computation-Guided Rational Design of a Peptide Motif That Reacts with Cyanobenzothiazoles via Internal Cysteine–Lysine Relay

Abstract: Site-selective protein modification based on covalent reactions of peptide tags and small molecules is a key capability for basic research as well as for the development of new therapeutic bioconjugates. Here, we describe the computation-guided rational design of a cysteine- and lysine-containing 11-residue peptide sequence that reacts with 2-cyanobenzothiazole (CBT) derivatives. Our data show that the cysteine residue reversibly reacts with the nitrile group on the CBT moiety to form an intermediate thioimida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 39 publications
3
14
0
Order By: Relevance
“…Recently, Brocchini and co‐workers demonstrated that a His‐Gly‐His tag could be conveniently modified with a bis‐sulfone reagent to site‐specifically alkylate various positions of interferon (IFN) with a 10 kDa PEG chain (Figure 6, panel B) [89] . In another recent example, Bertozzi and co‐workers reported the computational‐guided discovery of an 11‐amino acid tag (GGHPDPCPKGG) that undergoes a S‐to‐N transfer reaction to covalently modify Lys with a 2‐cyanobenzothiazole reagent (Figure 6, panel C) [90] . The conformation of this peptide tag is engineered to place the Cys and Lys residues in proximity, promoting the intramolecular transfer in a mechanism similar to native chemical ligation.…”
Section: Regioselectivity Driven By “Traceable”‐proximitymentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Brocchini and co‐workers demonstrated that a His‐Gly‐His tag could be conveniently modified with a bis‐sulfone reagent to site‐specifically alkylate various positions of interferon (IFN) with a 10 kDa PEG chain (Figure 6, panel B) [89] . In another recent example, Bertozzi and co‐workers reported the computational‐guided discovery of an 11‐amino acid tag (GGHPDPCPKGG) that undergoes a S‐to‐N transfer reaction to covalently modify Lys with a 2‐cyanobenzothiazole reagent (Figure 6, panel C) [90] . The conformation of this peptide tag is engineered to place the Cys and Lys residues in proximity, promoting the intramolecular transfer in a mechanism similar to native chemical ligation.…”
Section: Regioselectivity Driven By “Traceable”‐proximitymentioning
confidence: 99%
“…[89] In another recent example, Bertozzi and co-workers reported the computational-guided discovery of an 11-amino acid tag (GGHPDPCPKGG) that undergoes a S-to-N transfer reaction to covalently modify Lys with a 2-cyanobenzothiazole reagent (Figure 6, panel C). [90] The conformation of this peptide tag is engineered to place the Cys and Lys residues in proximity, promoting the intramolecular transfer in a mechanism similar to native chemical ligation.…”
Section: Covalent Labeling Via Tag-induced Reactivitymentioning
confidence: 99%
“…In addition, it is not clear whether alternative elimination pathways exist, stemming from the tetrahedral intermediate. Amidines, the products of thiolate expulsion, have been detected after CBT treatment of peptide sequences containing either N‐terminal cysteine or internal cysteine and lysine residues . Reversion from the tetrahedral intermediate back to the thioimidate through ring opening has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Amidines,t he products of thiolate expulsion, have been detected after CBT treatment of peptide sequences containing either N-terminal cysteine [13] or internal cysteinea nd lysine residues. [14] Reversion from the tetrahedral intermediate back to the thioimidate through ring opening has not been reported.…”
Section: Introductionmentioning
confidence: 99%